Factors influencing prospectives uses of ratten canes as furnish for cement composite production (2011)
This paper discusses the prospective uses of three readily available ratten canes in southern and western Nigeria namely: Laccosperma secundiflorum, Eremospatha macrocarpa, and Calamus deerratus as furnish for Cement Bonded Composites(CBCs) production. Advantages of utilising ratten canes as furnish for CBC production, limiting factors influencing the development of ratten composites and means of curtailment are examined. Ratten canes are potential furniture for CBC production but will require pre-treatment before use to ensure formation of strong crystalline bond.